f ( x ) = 2 x + 1 + 2 x − 1 4 x + 4 x 2 − 1
Find the value of f ( 1 ) + f ( 2 ) + ⋯ + f ( 4 0 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Perfect! Exactly what I wanted!
Did absolutely the same way.
After some calculations.
Just multiply numerator and denominator by ( 2 x + 1 − 2 x − 1 ) .
⇒ 2 x + 1 + 2 x − 1 4 x + 4 x 2 − 1 = 2 2 x + 1 ( 2 x + 1 ) + 2 x − 1 ( 1 − 2 x )
Now, putting x = 1 , x = 2 , x = 3 and x = 4 0 , we observe that all terms cancel leaving − 2 1 and 2 8 1 8 1 .
∴ 2 8 1 8 1 − 1 = 2 7 2 8 = 3 6 4
Nice observation, and I learned a new method for telescoping series.
Problem Loading...
Note Loading...
Set Loading...
Let 2 x + 1 = a , 2 x − 1 = b
S = x = 1 ∑ 4 0 a + b a 2 + b 2 + a b = x = 1 ∑ 4 0 a 2 − b 2 a 3 − b 3
∴ S = x = 1 ∑ 4 0 2 x + 1 − ( 2 x − 1 ) ( 2 x + 1 ) 2 3 − ( 2 x − 1 ) 2 3 = 2 ( 8 1 ) 2 3 − 1 = 3 6 4